Metformin Reduces Bleomycin-induced Pulmonary Fibrosis in Mice - Choi, Sun Mi (J Korean Med Sci, 2016)
Metformin has anti-inflammatory and anti-fibrotic effects. We investigated whether metformin has an inhibitory effect on bleomycin (BLM)-induced pulmonary fibrosis in a murine model. A total of 62 mice were divided into 5 groups: control, metformin (100 mg/kg), BLM, and BLM with metformin (50 mg/kg or 100 mg/kg). Metformin was administered to the mice orally once a day from day 1. We sacrificed half of the mice on day 10 and collected the bronchoalveolar lavage fluid (BALF) from their left lungs. The remaining mice were sacrificed and analyzed on day 21. The right lungs were harvested for histological analyses. The messenger RNA (mRNA) levels of epithelial-mesenchymal transition markers were determined via analysis of the harvested lungs on day 21. The mice treated with BLM and metformin (50 mg/kg or 100 mg/kg) showed significantly lower levels of inflammatory cells in the BALF compared with the BLM-only mice on days 10 and 21. The histological examination revealed that the metformin treatment led to a greater reduction in inflammation than the treatment with BLM alone. The mRNA levels of collagen, collagen-1, procollagen, fibronectin, and transforming growth factor-β in the metformin-treated mice were lower than those in the BLM-only mice on day 21, although statistical significance was observed only in the case of procollagen due to the small number of live mice in the BLM-only group. Additionally, treatment with metformin reduced fibrosis to a greater extent than treatment with BLM alone. Metformin suppresses the inflammatory and fibrotic processes of BLM-induced pulmonary fibrosis in a murine model.